The Role of Motivation as Mediating Relationship Between Incentives and Employee Performance - Nurlina; Edy Jumady (Jurnal Economic Resource, 2021)
The objective of this article is to study the relationship between performance incentives and employee motivation at PT. PELINDO IV The results of this research are drawn from a quantitative survey. This technique is referred to as random and proportional sampling. SmartPLS v.3.8 was employed in this study Incidentally, the results demonstrated that monetary incentives had a significant effect on motivation. With regard to productivity, the only thing that incentives do is to is move resources from one place to another. People who are motivated perform better. Incentives affect performance by influencing the degree of motivation, and performance is positively influenced by the medium of incentives.